Macropinocytosis dependent entry of Chikungunya virus into human muscle cells. - Ching Hua Regina Lee; Khairunnisa Mohamed Hussain; Justin Jang Hann Chu (Public Library of Science (PLoS), 2019)
Chikungunya virus (CHIKV) is a re-emerging arbovirus known to cause chronic myalgia and arthralgia with high morbidity. CHIKV is now considered endemic in many countries across Asia and Africa. In this study, the susceptibility of various human, mammalian and mosquito cell lines to CHIKV infection was evaluated. CHIKV infection was found to be cell-type dependent and virus strain-specific. Furthermore, SJCRH30 (human rhabdomyosarcoma cell line) was showed to be highly permissive to CHIKV infection, with maximum production of infectious virions observed at 12 h.p.i. Pre-infection treatment of SJCRH30 with various inhibitors of endocytosis, including monodansylcadaverine (receptor-mediated endocytic inhibitor), dynasore (clathrin-mediated endocytic inhibitor), as well as filipin (caveolin-mediated endocytosis inhibitor), resulted in minimal inhibition of CHIKV infection. In contrast, dose-dependent inhibition of CHIKV infection was observed with the treatment of macropinocytosis inhibitor, 5-(N-ethyl-N-isopropyl)amiloride (EIPA). Furthermore, siRNA-mediated knockdown of sortin nexin 9 (SNX9) a protein involved in macropinosome formation, also resulted in a significant dose-dependent reduction in viral titre. By performing a virus entry assay, CHIKV particles were also observed to colocalize with FITC-dextran, a macropinosome marker. This study shows for the first time, that the infectious entry of CHIKV into human muscle cells is mediated by macropinocytosis. Together, the data from this study may pave the way for the development of specific inhibitors that target the entry process of CHIKV into cells.